Cartografias do cotidiano: memórias e narrativas em espaços escolares e não escolares sobre a infância psiquiatrizada - Andreata, Marilia Rodrigues (2022)
This work seeks to understand how childhoods have been crossed by the processes of psychologicalization of education in school and non-school spaces. Through the brands that were produced through the experiences lived and built with children, teachers and families, at school and in a clinical environment, this work aimed to understand in what ways education can be captured by the regulatory devices of inclusion/exclusion of the child through psychiatric discourses in this daily life. For this, cartography was used as a research methodology, having as methodological resources the production of narratives, memory and the use of field diary. The narratives woven in the text refer mainly to the memories of the dialogues between Special Education, disability, difference and how they intertwine with Education and Inclusion. The choice of memory use as a resource was because this work was located in different periods in which education was present in my career as a researcher, including the time before the writing of the dissertation. The concept of intercessors, from Deleuze, composes the process of construction of analyses and writing itself, seeking to relate the concepts of Special Education, Psychoquiatrization, from a Foucaultian reading, from the discussions of mental asylum, aligning them to the narratives that were produced in these daily lives. The narratives of everyday life point to the bet of inventive and sensitive practices as powerful escape lines of the psychiatric processes of childhoods